Succession Planning and Family Business Continuity: Perspectives from Lagos State, Nigeria (Global Journal of Management and Business Research, 2022)
Environment scrutiny has shown that family businesses are the common form of business in Nigeria and their going concern has generated academic debate and public discourse worldwide. Yet, the features orchestrating continuity in these family businesses are different and geographically diverse. One of the major issues to which this can be attributed to is the uncommonness of adequate succession planning practices. The objective of this paper is to examine the effect of succession planning on family business continuity in Lagos State, Nigeria. A survey research design was adopted for this paper with 503 selected SMEs operating in Lagos State as the target population. Taro Yamane sample size method was adopted and data was collected through the use of structured questionnaire adapted and validated for the study. The Cronbach#x2019;s alpha coefficient for the questionnaire items ranges between 0.850 and 0.775. The questionnaire response rate was 93.20%. The gathered data were analyzed using descriptive and inferential (Pearson product moment correlation and regression analysis) statistics. The analysis of the data revealed that succession planning had a significant effect on family business continuity (R=0.738, R 2 =0.545, Adj. R 2 = 0.538, F (78.821) =1.95); plt;0.05). This paper concluded that, succession planning is pertinent to the enhancement of continuity in family businesses in Lagos State. The paper therefore, recommend that for family businesses to continue to perform and achieve continuity, succession planning must be put into strategic plan of the organization so that employees have adequate leadership competence and mentoring culture.
Keywords: business continuity; family business; mentoring; performance; resources; succession planning